GAYA KEPEMIMPINAN DEMOKRASI MAHASISWA TERHADAP KKNI - Megawati Megawati; Dini Fitriani2; Neng Nurwiatin; Ivon Mukaddamah (Sekolah Tinggi Pariwisata Mataram, 2022)
Leadership is the way a leader influences the behavior of subordinates to want to work together and work effectively and efficiently to achieve organizational goals. Democratic leadership, also known as participatory leadership, is a type of leadership style in which group members take a more participatory role in the decision-making process. This study aims to evaluate the implementation of the IQF curriculum to determine the effect of students' democratic leadership style on the IQF. The sample used in this study amounted to 45 respondents from 157 students. Data collection techniques are through interviews, observations, and documentation studies. The results obtained in this study are the process of completing the KKNI task. The democratic style plays a very important role in stimulating student motivation in assignments. Active students will definitely get good results in working on KKNI assignments. With the research that has been carried out, it appears that the implementation of the IQF in the student learning process has been said to be good, although it still needs improvement in aspects such as plagiarism and others.